Criminally Queer Homosexuality and Criminal Law in Scandinavia 1842-1999 - Rydström, Jens (Aksant Academic Publishers, 2007)
This book provides a coherent history of criminal law and homosexuality in Scandinavia 1842-1999, a period during which same-sex love was outlawed or subject to more or less severe legal restrictions in the Scandinavian penal codes. This was the case in most countries in Northern Europe, but the book argues that the development in Scandinavia was different, partly determined by the structure of the welfare state. Five of the most experienced scholars of the history of homosexuality in the region (Jens Rydström, Kati Mustola, Wilhelm von Rosen, Martin Skaug Halsos and Thorgerdur Thorvaldsdóttir) describe how same-sex desire has been regulated in their respective countries during the past 160 years. The authors with their backgrounds in history, sociology, and gender studies represent an interdisciplinary approach to the problem of criminalization of same-sex sexuality. Their contributions, consisting for the most part of previously unpublished material, present for the first time a comprehensive history of homosexuality in Scandinavia. Among other things, it includes the most extensive study yet written in any language about Iceland's gay and lesbian history. Also for the first time, the book discusses in detail same-sex sexuality between women before the law in modern society and presents previously unpublished findings on this topic. Female homosexuality was outlawed in Eastern Scandinavia, but not in the Western parts of this region. It also analyzes the modern tendency to include lesbian women in the criminal discourse as an effect of the medicalization of homosexuality and the growing influence of medical discourse on the law.